METAVERSE STRATEGY AND PLANNING AT THE NATIONAL GALLERY - Nugraha, Rizki Nurul; Sesar Yuni Purwati, Anisa (Jurnal Hospitality dan Pariwisata, 2025)
This research examines how the strategy and planning of metaverse in the National Gallery. The purpose of this research is to find out and learn how the right strategy and planning in tourism, especially at the National Gallery tourist attraction. The research method used is the literature study method by collecting library data, reading and recording, and processing research materials. The results show that regarding the strategy of Augmented Reality (AR) and Virtual Reality (VR) technology that will be carried in the development of Metaverse and analysis of the use of information media, it can be summarized and concluded that Metaverse has considerable potential and opportunities as information media and the latest interactive educational media for the National Gallery.Keywords:  Metaverse, Augmented Reality (AR), Virtual Reality (VR), Strategy of Metaverse, Metaverse Planning, National Art Gallery